(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Many people experience overheating and poor ventilation due to years of research by scientists and technologists. It’s one of the reasons we don’t have a better environment. The researchers came up with an idea to make a device that solved this problem. Using solar panels, this device reduces heat and saves energy. The device is also operated by a sensor that allows an exhaust fan to work automatically by maintaining room temperature. The results of the research study present the prototype design, control system, and circuit connection. Arduino IDE has been used to program the Arduino Uno, MAX6675 thermocouple, and MQ135 sensor. It is also programmed in Arduino IDE with downloaded libraries. Depending on the sensors determine the exhaust fan speed. If the sensor reaches 34°C-40°C, the exhaust fan will operate at Normal, Moderate, and Maximum. When the Mq135 sensor detects toxic gas, the exhaust fan will run at Maximum speed. The result shows voice recognition has no delay in manually operating the device using voice. The result shows that a solar panel can produce 18-20 watts per hour, depending on the weather. The respondents’ perceptions of the prototype reliability were gathered through a questionnaire. The demographic profile of the respondents, where age, sex, and educational attainment are determined and presented using a pie graph. The voice recognition and sensor solar panel exhaust fan is sensor-based and uses voice recognition to operate the device manually, and the MAX6675 K- -type thermocouple, MQ135 Gas, operates automatically. The components used were compatible with the Arduino Uno. It successfully runs the prototype operations, the sensors’ detection, and the speech manually. A majority of respondents are males aged 29-40. Graduates make up 47% of respondents on educational attainment. The evaluation shows that the target client agrees with the proposed prototype since the weighted mean of all indicators indicates more than 3, according to the Likert scale rating. The researchers conclude that a microcontroller Arduino Uno is an effective device for developing a Voice recognition and sensor solar panel exhaust fan device.